DOI: 10.1007/978-3-540-85379-4_37
|View full text |Cite
|
Sign up to set email alerts
|

Smart Home Technology for the Elderly: Perceptions of Multidisciplinary Stakeholders

Abstract: The "implementation" and use of smart home technology to lengthen independent living of non-instutionalized elderly have not always been flawless. The purpose of this study is to show that problems with smart home technology can be partially ascribed to differences in perception of the stakeholders involved. The perceptual worlds of caregivers, care receivers, and designers vary due to differences in background and experiences. To decrease the perceptual differences between the stakeholders, we propose an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…These stakeholders involved in our ethical analysis had been previously defined by various authors (Allen et al, 2008;Duquenoy and Whitehouse, 2006;Duquenoy, 2004;Hofmann, 2012;R. Sparrow and L. Sparrow, 2006;Sponselee et al, 2008;van Hoof et al, 2011). For all these stakeholders we have listed the ethical issues present in the group of relevant articles that occur in three different stages of the technology: R&D, clinical trials, and clinical application.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These stakeholders involved in our ethical analysis had been previously defined by various authors (Allen et al, 2008;Duquenoy and Whitehouse, 2006;Duquenoy, 2004;Hofmann, 2012;R. Sparrow and L. Sparrow, 2006;Sponselee et al, 2008;van Hoof et al, 2011). For all these stakeholders we have listed the ethical issues present in the group of relevant articles that occur in three different stages of the technology: R&D, clinical trials, and clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…With correct motivation, a greater intention to use the ICT devices can be reached by the elderly (Zaad and Ben Allouch, 2008) who are willing to accept technology if it is worth the effort (Wallace et al, 2010). It has been reported that designers are usually less successful than relatives in motivating users to use ICT devices (Sponselee et al, 2008). Relatives can have a major impact on PwD's subjective norms for ICT acceptance (Steve Lauriks et al, 2010;Zaad and Ben Allouch, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations